Competência Percebida e Realização Escolar: Que Relações em Alunos do Ensino Secundário? - Stocker, Joana (2010)
Do pupils with high levels of perceived competence (emotional competence, personal conceptions of intelligence, self-efficacy, self-concept and causal dimensions) achieve better academic performance? In order to find out, we conducted a study with 385 secondary school pupils from Porto. There were administered the Composite Questionnaire of Perceived Competence (Faria, Stocker & Pina Neves, 2009), with 162 items, and a Socio-Demographic Questionnaire, with 23 items. Correlation analyses indicated that academic self-concept and academic self-efficacy are the motivational constructs most related to achievement, followed by causal dimensions, emotional competence and personal conceptions of intelligence. Multiple linear regression analyses for Portuguese, Mathematics and global point average revealed academic self-concept, academic self-efficacy, and personal conceptions of intelligence as the main achievement predictors: high perceptions of competence and efficacy, and static conceptions influence positively the achievement, explaining each model 44%, 53%, and 47% of total variance, confirming the importance of perceived competence on academic success.